Platinum, palladium, rhodium, molybdenum and strontium in blood of urban women in nine countries - Rentschler, Gerda; Rodushkin, Ilia; Cerna, Milena; Chen, Chunying; Harari, Florencia; Harari, Raúl; Horvat, Milena; Hruba, Frantiska; Kasparova, Lucie; Koppová, Kvetoslava; Krskova, Andrea; Krsnik, Mladen; et al. (International journal of hygiene and environmental health, 2018)
BACKGROUND: There is little reliable information on human exposure to the metals platinum (Pt), palladium (Pd) and rhodium (Rh), despite their use in enormous quantities in catalytic converters for automobile exhaust systems. OBJECTIVES: To evaluate blood concentrations of Pt (B-Pt), Pd (B-Pd) and Rh (B-Rh) in women from six European and three non-European countries, and to identify potentially influential factors. In addition, molybdenum (Mo) and strontium (Sr) were analysed. METHODS: Blood from 248 women aged 47-61 was analysed by high resolution inductively coupled plasma mass spectrometry under strict quality control. RESULTS: The medians were: B-Pt 0.8 (range <0.6-5.2), B-Pd <5 (<5-9.3), B-Rh <0.4 (<0.4-3.6)ng/L and B-Mo 2.0 (0.2-16) and B-Sr 16.6 (3.5-49) μg/L. Two women with highly elevated B-Pt (242 and 60ng/L), previously cancer treated with cis-platinum, were not included in the data analysis. All elements varied geographically (2-3 times) (B-Pd P=0.05; all other elements P<0.001); variations within each area were generally 5-10 times. Traffic was not associated with increased concentrations. CONCLUSIONS: General population blood concentrations of Pt, Pd and Rh are within or below the single digit ng/L range, much lower than in most previous reports. This is probably due to improved analytical performance, allowing for more reliable information at ultra-trace levels. In general, Mo and Sr agreed with previously reported concentrations. All elements showed geographical and inter-individual variations, but no convincing relationships with self-reported traffic intensity were found. Pt from the antineoplastic drug cis-platinum is retained in the body for years.
Keywords: Platinum; platina; Female; Cities; molybden; ženské pohlaví; monitorování životního prostředí; Strontium; velkoměsta; lidé; Rhodium; Molybdenum; palladium; těžké kovy; Environmental Monitoring; rhodium; lidé středního věku; stroncium; Metals, Heavy; Palladium; Middle Aged; Humans